Gambaran Kesehatan Mental pada Ibu Post Natal - Keny Nurchaeni Cahyaningtyas; Vinami Yulian (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the description of mental health in postnatal mothers. The research method used is quantitative descriptive research. The results showed that the characteristics of the respondents, based on the age of the majority aged 20-35 years, were 73.8%, with high school/vocational school education of 54.8% and the status of housewives of 59.5%, married status of 97.6% with normal delivery as much as 54.8%, number of parity 2 as much as 52.4%. based on the results of the univariate test it was found that the majority of mothers experienced major depression as much as 64.3%. In conclusion, postnatal mothers in Gatak Village need special attention because the majority of postnatal mothers have severe mental health. Keywords: Mental Health, Post Natal